On the Premises of Regulating the Principles of Remuneration of the Legal Profession – A Legal and Economic Analysis - Kamil DABROWSKI (Communications of International Proceedings, 2021)
The status of the legal profession, accommodated within the so-called liberal professions, is the subject of interest of various legal scholars and commentators. Despite that, it is not only difficult to find studies that address the issue of the legal status of this type of profession, its occupational privileges or principles of disciplinary liability, but also those that focus on the legitimization and the desired state of regulation of the principles of remuneration of the legal profession. Recognizing this gap, this study addresses the aforementioned issues in the legal and economic perspective. Starting from the general reflection about the reasons for establishing these legal regulations, the author puts forward a thesis about an inseparable relationship between the establishment of clear rules for remuneration of legal professions and the protection of interests of their clients. Then, by describing the regulator’s current approach to this matter, the author points out and justifies a need to establish restrictions in terms of the application of success fee clauses in contracts for the provision of legal services.
Keywords: Legal Professions; Remuneration of Legal Professions; Information Asymmetry